Evaluation of teaching digital competence and quality in initial training in students of the X cycle of the UNMSM Professional School of Education - 2020 - Silva Rodas , Jasming Edith (2024)
At a global level, therefore, in our country, the demand for teachers with digital skills is growing, which is why our research carries out the relationship between the evaluation of the teacher's digital skills and the quality in the initial training of the student of the X cycle of education of San Marcos in Lima. A quantitative approach, hypothetical deductive method, ordinal level and correlational design allows us a descriptive correlational study in 30 teachers, the participants completed a survey that was validated by three expert juries and the reliability was measured by the Crombach Alpha statistician, thus ensuring the high reliability of the two study variables. Descriptive statistics and inferential statistical analysis were used to find the results, it is shown that the evaluation between teaching digital competence and quality of initial training is, 437 and, since the significance value is less than 0.01, the hypothesis is rejected. null and it is indicated that there is a statistically significant, average evaluation between the two study variables.